Implementing Standardized Patient Caregivers to Practice Difficult Conversations in a Pediatric Dentistry Course - Beau D. Meyer; Bethany Fearnow; Hannah L. Smith; Sarah G. Morgan; Rocio B. Quinonez (Association of American Medical Colleges, 2022)
Introduction Standardized patient (SP) methodology has been used in health professional education to help students develop communication, deeper diagnostic reasoning, and critical thinking skills. Few examples demonstrate the use of SPs to practice difficult conversations with pediatric caregivers in the pediatric dentistry literature. The objective of this educational activity was to describe the implementation of three SPs in a pediatric dentistry course for second-year dental students. Methods We developed three SP encounters covering interactions with caregivers of an infant with severe early childhood caries, an adolescent on the path to gender affirmation, and a child with autism and dental caries whose caregiver was resistant to fluoride- and silver-containing dental materials. We describe the case design process, rubric construction and calibration, student debriefing, and pandemic modifications. We evaluated the effectiveness of the implementation by thematic analysis of student reflections following each encounter using a qualitative descriptive framework. Results Eighty-three students completed each encounter. Qualitative analysis showed that students preferred a more realistic encounter by having a child or other distraction present. Students relied on different elements of motivational interviewing depending on the objective of each encounter and the age of the patient. Overall, the SP encounters were well received by students and faculty as an alternative or supplement to traditional student evaluation methods. Discussion We noted a number of lessons learned about implementing SP methodology in pediatric dental education. With these experiences now in place, future evaluations should measure student performance in the SP encounters against student performance during clinical care.